A novel implantable device for sensory and affective assessment of orofacial pain in rats - Huang, Xiaoling; Li, Zhenxing; Ma, Jiahui; Huang, Dong; Yan, Xuebin; Zhou, Haocheng (Frontiers in Veterinary Science, 2022)
Background and objective: Orofacial pain, in particular, chronic orofacial pain remains a great challenge in clinical practice. To better understand the underlying mechanism of disease, it is essential to apply a feasible and stable preclinical measurement of facial pain. Here, we introduced a novel electrical noxious stimulator in freely behavioral rodents and examined its validation in both naïve and chronic orofacial pain animals. Methods: One subcutaneous device of electrical stimulator was implanted in the facial region for delivery of the nociceptive input. The sensory component of orofacial pain was assessed by response scoring tool, and conditioned place aversion (CPA) paradigm for pain affect respectively. To confirm its usage in chronic pain state, the chronic constriction injury of the infraorbital nerve (ION-CCI) model was then applied. Results: We found that responsive scores increased with stimulation intensity, and acted in a dosage-dependent manner, which can be attenuated by the administration of morphine intraperitoneally. Naïve rats displayed significant aversive reaction to the noxious electrical stimulation (25 volts) in the CPA testing. In addition, an obvious sensory hypersensitivity to electrical stimulation was confirmed by the increased response scores in ION-CCI rats. Furthermore, ION-CCI animal showed significant avoidance to electrical stimulation at relatively low intensity (10 volts), which was innoxious to naïve rats. Conclusions: Our findings may provide an alternative pre-clinical measurement of orofacial pain, to quantitively assess both sensory and affective component of orofacial pain.